Hydromechanical Automatic Transmission - Lubos Kucera; Michal Lukac; Ladislav Jurak; Frantisek Brumercik (Communications - Scientific letters of the University of Zilina, 2009)
This contribution describes some tests of hydromechanical infinitely variable transmission (IVT) on a test stand. Further, there is described a truck with installed IVT and tests of this IVT at real conditions. There is also shown a control system of the IVT.